Sposoby kuracji różnych dolegliwości laryngologicznych i stomatologicznych według „Compositiones medicamentorum” rzymskiego lekarza Skryboniusza Largusa — przekład z łaciny - Katolo, Artur (Collectanea Philologica, 2025)
Scribonius Largus’s (1st-century) Compositiones Medicamentorum is one of the most important sources in the history of medicine. The recipes it contains were used in European medicine until the end of the 17th century. The purpose of this article is to present [translated from Latin] the methods of treating laryngological and dental ailments according to the recipes of this ancient Roman physician.